222 IS GASTROESOPHAGEAL REFLUX DISEASE MORE PREVALENT IN PATIENTS WITH MONOCLONAL GAMMOPATHY OF UNDETERMINED SIGNIFICANCE?. Issue 1 (1st January 2007) - Singh, J.; Malani, A. K.; Pabla, M.; Vaka, S.; Patel, V.; Gupta, C.; Kambhampati, S.
Abstract : Background: The prevalence of clinically significant gastroesophageal reflux (GERD) in the general population varies between 3 and 6%. We observed GERD to be one of the major complaints of our patient population with monoclonal gammopathy of unknown significance (MGUS). There is no literature available on the incidence of GERD in MGUS. Moreover, there have been conflicting reports on the prevalence of Helicobacter pylori and MGUS. Objective: To study the incidence and relationship of GERD, H. pylori, and MGUS. Methods: We identified 394 patients with MGUS at Veterans Affairs Medical Center, Kansas City, diagnosed over the last 20 years. The control group consisted of patients with chronic lymphocytic leukemia (CLL) followed over the same period (20 years) at the same institution. Charts on these patients were reviewed for endoscopic findings, pathologic biopsies, and H. pylori staining on histology. Results: Forty-one percent (162/394) of patients with MGUS were noted to have moderate to severe symptoms of GERD compared with 10% (47/460) in the control group. The median age of the patients was similar in both groups. Sixty percent (97/162) of MGUS patients with GERD underwent endoscopies compared with 25% (12/47) of patients in the control group. Histology was positively stained for H. pylori in 27.8% patients (27/97) in MGUS and 25% (3/12) of the control group. We found no correlation between H. pylori positivity and type or level of monoclonal protein in MGUS. In addition, we observed no change in immunoglobulin levels following treatment and eradication of H. pylori in MGUS patients. Conclusion: At our institution, patients with MGUS have a higher prevalence of GERD. Our findings need to be confirmed and verified in further prospective studies. No correlation was seen between H. pylori infection and MGUS.